2017
DOI: 10.1055/s-0043-117150
|View full text |Cite
|
Sign up to set email alerts
|

Erweiterte pathohistologische Kriterien zur Bewertung der Langzeitprognose des Magenkarzinoms

Abstract: Zusammenfassung Hintergrund Das Magenkarzinom zählt zu den häufigsten Tumorerkrankungen weltweit. Trotz zahlreicher Innovationen in der Diagnostik und Therapie ist die Prognose weiterhin schlecht, da die Detektion der Erkrankung auf tumorassoziierte Symptome angewiesen ist, welche in der Mehrzahl der Fälle spät auftreten. Eine weitere Verbesserung der Behandlungsergebnisse kann durch eine differenziertere und individuellere Bewertung der Tumorbiologie erzielt werden. Wir stellen hierzu eine umfangrei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…The patients with those characteristics have poor survival time. The results were basically consistent with other statistical reports [29][30][31]. As for the lymphadenectomy extent, Sano et al enrolled 505 patients in his research showed no survival difference between SD2 group and MD2 group in AGC patients [32].…”
Section: Discussionsupporting
confidence: 89%
“…The patients with those characteristics have poor survival time. The results were basically consistent with other statistical reports [29][30][31]. As for the lymphadenectomy extent, Sano et al enrolled 505 patients in his research showed no survival difference between SD2 group and MD2 group in AGC patients [32].…”
Section: Discussionsupporting
confidence: 89%